2018
DOI: 10.12659/msm.912643
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of KIF22/Kinesin-Like DNA Binding Protein (Kid) as a Poor Prognostic Factor in Prostate Cancer Patients

Abstract: BackgroundKid (kinesin-like DNA binding protein), a member of microtubule-dependent molecular motor proteins, also known as KIF22, is reported to be associated with carcinogenesis and cancer progression in different types of malignant tumor, but the biologic behavior and clinical outcome of KIF22 in prostate cancer (PCa) has not been well studied. This study aimed to analyze the association between KIF22 and clinical outcome in PCa patients.Material/MethodsThe expression of KIF22 in tumor specimens compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Suppression of KIF22 inhibits cancer cell proliferation through delaying mitotic exit [ 28 ]. Zhang et al [ 29 ] indicated that KIF22 was associated with clinical outcome and tumor progression in prostate cancer. KIF22 is involved in the migration and proliferation of gastric cancer cells through MAPK-ERK pathways [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of KIF22 inhibits cancer cell proliferation through delaying mitotic exit [ 28 ]. Zhang et al [ 29 ] indicated that KIF22 was associated with clinical outcome and tumor progression in prostate cancer. KIF22 is involved in the migration and proliferation of gastric cancer cells through MAPK-ERK pathways [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Except for KIF14, multiple members of kinesin family are involved in tumorigenes and could serve as prognostic predictor of several types of cancers [28]. High expression of KIF22 and KIF15 could be poor prognostic factors in patients with prostate cancer and lung adenocarcinoma, respectively [29,30]. In addition, KIF20A is correlated with unfavorable clinical outcome and the…”
Section: Discussionmentioning
confidence: 99%
“…114 PCa patients were collected from the Second Hospital of Tianjin Medical University; all the patients had signed an informed consent form [18]. The tissue from these patients who underwent radical prostatectomy between July 2016 and October 2017 were paraffin-embedded for immunohistochemistry analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The proportion of tumor cells was graded from 0 to 2: 0 points (<5%), 1 point (5%–50%), 2 points (>50%). The sum of scores represented the expression levels: 0~2 points as low expression and 3~4 points as high expression [18]. The mean score from two pathologists was used as the final immunostaining score.…”
Section: Methodsmentioning
confidence: 99%